Religiosity and teen birth rate in the United States - Strayhorn Joseph M; Strayhorn Jillian C (BMC, 2009)
Abstract Background The children of teen mothers have been reported to have higher rates of several unfavorable mental health outcomes. Past research suggests several possible mechanisms for an association between religiosity and teen birth rate in communities. Methods The present study compiled publicly accessible data on birth rates, conservative religious beliefs, income, and abortion rates in the U.S., aggregated at the state level. Data on teen birth rates and abortion originated from the Center for Disease Control; on income, from the U.S. Bureau of the Census, and on religious beliefs, from the U.S. Religious Landscape Survey carried out by the Pew Forum on Religion and Public Life. We computed correlations and partial correlations. Results Increased religiosity in residents of states in the U.S. strongly predicted a higher teen birth rate, with r = 0.73 (p < 0.0005). Religiosity correlated negatively with median household income, with r = -0.66, and income correlated negatively with teen birth rate, with r = -0.63. But the correlation between religiosity and teen birth rate remained highly significant when income was controlled for via partial correlation: the partial correlation between religiosity and teen birth rate, controlling for income, was 0.53 (p < 0.0005). Abortion rate correlated negatively with religiosity, with r = -0.45, p = 0.002. However, the partial correlation between teen birth rate and religiosity remained high and significant when controlling for abortion rate (partial correlation = 0.68, p < 0.0005) and when controlling for both abortion rate and income (partial correlation = 0.54, p = 0.001). Conclusion With data aggregated at the state level, conservative religious beliefs strongly predict U.S. teen birth rates, in a relationship that does not appear to be the result of confounding by income or abortion rates. One possible explanation for this relationship is that teens in more religious communities may be less likely to use contraception.